Обнаружение импульсами волн Релея несплошностей поверхности металлоизделий, имеющих сложную форму - Плеснецов, Сергей Юрьевич; Мигущенко, Руслан Павлович; Сучков, Григорий Михайлович; Петрищев, Олег Николаевич; Митин, Александр Владимирович (НТУ "ХПИ", 2016)
В статье приводится экспериментальное исследование в области ультразвуковой дефектоскопии. Установлено, что при отражении поверхностной волны происходит трансформация волны Релея на кромке изделия. Экспериментально подтвержден факт формирования поверхностной волны за пределами острой кромки. Для возбуждения и приема импульсов волн Релея, традиционно применяли пьезоэлектрические преобразователи, однако их точность недостаточна из-за применения контактной жидкости. Подтверждена эффективность применения совмещенных ЭМА-преобразователей для обнаружения поверхностных дефектов и выявляемость дефектов поверхности за пределами резкого изменения формы поверхности объекта контроля. Выявлены условия принятия максимального сигнала от поверхностной волны.

The article presents an experimental research in the field of ultrasonic testing. It is established that the reflection of the surface wave is based on the transformation of Rayleigh wave on the edge of the item. Rayleigh waves have the advantage, due to relatively little attenuation as they propagate along the surface of the material, including those having a curved shape. Experiments confirmed the fact of the formation of surface waves beyond the sharp edge. For the excitation pulse and receiving of Rayleigh waves, conventionally piezoelectric transducers are used. This type of converters involves the use of contact fluid for signal transmission. This factor leads to a significant reduction of accuracy and limits the usefulness of the piezoelectric transducers in the inspection. It is possible to eliminate the above contradiction by applying methods of surface excitation and reception of ultrasonic pulses without couplant, such as, for example, – electromagnetic acoustic transducer. The efficacy of combined EMA-transducers for detecting surface defects and surface defects detection outside the abrupt change in the surface shape of the object of control is affirmed. The conditions for the adoption of maximum signal of the surface wave.
Rayleigh wave pulse detection of discontinuities on complex-shaped metal surfaces
Keywords: ультразвуковое исследование; ЭМА преобразователи; объект контроля; трансформация волны; ultrasound; Rayleigh wave; EMA transducers; monitoring object; transformation of the wave